Infection dynamics of endosymbionts reveal three novel localization patterns of Rickettsia during the development of whitefly Bemisia tabaci. Issue 11 (18th August 2018) - Shi, Pei-Qiong; Wang, Lei; Liu, Yuan; An, Xuan; Chen, Xiao-Sheng; Ahmed, Muhammad Z; Qiu, Bao-Li; Sang, Wen
ABSTRACT: The whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) is a severe agricultural pest that harbors at least seven endosymbionts. Many important aspects of the symbiosis mechanism between these bacterial endosymbionts and their hosts are poorly understood, such as endosymbiont proliferation dynamics, spatial distribution and titer regulation during host development. In this study, infection by bacterial endosymbionts in the whitefly B. tabaci Middle East-Asia Minor-1 (MEAM1, formerly B biotype) South China population, their infection titers in various stages of whitefly host development and their spatial localization were investigated. Results revealed that the MEAM1 B. tabaci harbors the primary symbiont Portiera and secondary symbionts Rickettsia and Hamiltonella . The titers of these three endosymbionts increased with the development of their B. tabaci host. Significant proliferation of Portiera and Hamiltonella mainly occurred during the second to fourth instar nymphal stages, while Rickettsia proliferated mainly during adult eclosion. Fluorescence in situ hybridization analysis of B. tabaci adults revealed three novel infection patterns of Rickettsia : assemblage in the bacteriocytes that scattered through the entire abdomen of the female host, localization in wax glands and localization in the colleterial gland. These novel infection patterns may help to uncover the function of Rickettsia in its insect hosts. Abstract : Three novel infection patterns for Rickettsia endosymbiont in the whitefly Bemisia tabaci were identified, including being scattered in bacteriocytes throughout the female abdomen, and localization in wax glands and the colleterial gland.